Diagnóstico serológico de leptospirosis en el rebaño de alpacas del cantón Mejía parroquia Machachi localidad de Wasillama para tomar medidas sanitarias. - Jessica Elizabeth, Andagana Chango (2021)
This research was had relevant in the serological diagnosis of Leptospira in South American camelids (alpacas), which are found in the moor of the Pichincha province, Mejía canton, Machachi parish, locality of Wasillama, at 3600 meters above sea level. For the study, 40 adult alpacas of age between 3 and 5 years of both sexes were randomly selected to take a blood sample from the femoral vein and collect in an anticoagulant vacutainers tube in the amount of 5 ml of blood which are labeled and transported in Cooler for their conservation to the ANIMALAB laboratory that is located in the city of Machachi to perform the tests using Microagglutination Serology (MAT). The results after using Microagglutination Serology (MAT) were 13 positive (+) and 27 negative (-) animals. Through the calculation of the data it was determined that 10.82% of the total camelids analyzed are infected. Also through this diagnosis it was determined that infected animals are carriers of serovar Leptospirosis Pomona and Leptospirosis Canicola.